2007
DOI: 10.1016/j.immuni.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for a Drosophila E3-Ubiquitin Ligase in Phagocytosis of Apoptotic Cells

Abstract: Many cells die by apoptosis during animal development. Apoptotic cells are rapidly removed through phagocytosis by their neighbors or by macrophages. To genetically dissect this process, we performed an in vivo screen for genes required for efficient phagocytosis of apoptotic cells by Drosophila macrophages and identified pallbearer (pall), which encodes an F box protein. F box proteins generally provide substrate specificity to Skp Cullin F box (SCF) complexes, acting as E3 ligases that target phosphorylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
61
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 52 publications
4
61
0
Order By: Relevance
“…Similar results were obtained with DD1; hmlGAL4 and DD1; hmlGAL4; UAS-ICE. colleagues showed that a gain-of-function allele of Toll (Toll10B) was able to induce spz expression in the absence of immune challenge (Senger et al, 2006). We expressed the same Toll allele through a UAS construct in the haemocytes using crq-GAL4 (Silva et al, 2007). This is a GAL4 driver expressed in the pattern of croquemort, a gene coding for a macrophage-specific receptor of apoptotic corpses (Franc et al, 1996).…”
Section: Drs-gfp Induction In the Fat Body Is Influenced By The Absenmentioning
confidence: 99%
“…Similar results were obtained with DD1; hmlGAL4 and DD1; hmlGAL4; UAS-ICE. colleagues showed that a gain-of-function allele of Toll (Toll10B) was able to induce spz expression in the absence of immune challenge (Senger et al, 2006). We expressed the same Toll allele through a UAS construct in the haemocytes using crq-GAL4 (Silva et al, 2007). This is a GAL4 driver expressed in the pattern of croquemort, a gene coding for a macrophage-specific receptor of apoptotic corpses (Franc et al, 1996).…”
Section: Drs-gfp Induction In the Fat Body Is Influenced By The Absenmentioning
confidence: 99%
“…It remains to be seen if key engulfment receptors such as Draper and Croquemort in Drosophila, or their mammalian counterparts are ubiquitylated. However, it is noteworthy that Pall-deficient macrophages still possess the ability to take up AcLDL via the scavenger receptor pathway, further supporting the idea that Pall-SCF may function specifically in the context of apoptotic cell recognition by engulfment receptors 15 .…”
mentioning
confidence: 73%
“…Recently Nathalie Franc and colleagues have demonstrated for the first time a role for the SCF-ubiquitylation complex in the uptake of apoptotic cells by macrophages 15 . In this study, Drosophila embryos containing genomic deletions were screened for a failure to efficiently engulf apoptotic cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations